Structure of the DOCK2−ELMO1 complex provides insights into regulation of the auto-inhibited state - Leifu Chang; Jing Yang; Chang Hwa Jo; Andreas Boland; Ziguo Zhang; Stephen H. McLaughlin; Afnan Abu-Thuraia; Ryan C. Killoran; Matthew J. Smith; Jean-Francois Côté; David Barford (Nature Communications, 2020)
DOCK2 is a guanine nucleotide exchange factor (GEF) that activates RHO GTPases and interacts with ELMO1, which stimulates its GEF activity. Here, the authors provide mechanistic insights into how ELMO1 regulates DOCK2 activity by determining the structure of the DOCK2–ELMO1 binary complex representing the closed, auto-inhibited state and the DOCK2−ELMO1−RAC1 ternary complex structure, where DOCK2−ELMO1 adopts an open, active conformation.